2022
DOI: 10.30541/v46i4iipp.1137-1153
|View full text |Cite
|
Sign up to set email alerts
|

Household’s Willingness to Pay for Safe Drinking Water: A Case Study of Abbottabad District

Abstract: Safe drinking water is the basic need of each human being. In the past 100 years the world population tripled, but water use for human purposes multiplied sixfold [Frank, et al. (2000)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 13 publications
3
38
0
1
Order By: Relevance
“…Many existing studies analyze household choice of drinking water source through an averting (or defensive) expenditures and willingness to pay framework. Utilizing households' stated preferences for various drinking water alternatives, these microeconomic approaches attempt to quantify household demand for clean water and thereby evaluate the value of improvements in water quality (Akter, 2008;Dupont & Jahan, 2012;Haq et al, 2007;Jordan & Elnagheeb, 1993;Katuwal & Bohara, 2011;Larson & Gnedenko, 1999;McConnell & Rosado, 2000;Nauges & Van Den Berg, 2009;Pattanayak et al, 2005;Rodríguez-Tapia et al, 2017;Vasquez et al, 2009). Due to the reliance on in-depth survey assessments of household revealed preferences, these studies are necessarily small-scale, analyzing the choices of a few hundred households or less.…”
Section: 1029/2017wr022186mentioning
confidence: 99%
“…Many existing studies analyze household choice of drinking water source through an averting (or defensive) expenditures and willingness to pay framework. Utilizing households' stated preferences for various drinking water alternatives, these microeconomic approaches attempt to quantify household demand for clean water and thereby evaluate the value of improvements in water quality (Akter, 2008;Dupont & Jahan, 2012;Haq et al, 2007;Jordan & Elnagheeb, 1993;Katuwal & Bohara, 2011;Larson & Gnedenko, 1999;McConnell & Rosado, 2000;Nauges & Van Den Berg, 2009;Pattanayak et al, 2005;Rodríguez-Tapia et al, 2017;Vasquez et al, 2009). Due to the reliance on in-depth survey assessments of household revealed preferences, these studies are necessarily small-scale, analyzing the choices of a few hundred households or less.…”
Section: 1029/2017wr022186mentioning
confidence: 99%
“…Based on a household survey conducted in Abbottabad (Pakistan), Haq et al (2007) found that there are statistically significant effects of education on the water purification behaviour of the households. They also found that, higher income quartile is highly significant in all coping strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many such studies are, however, undertaken for policy purposes and are not published in academic journals. The published studies of WTP for improved water services in South Asia include Altaf, Jamal, and Whittington (1992), Haq, Usman, and Ahmad (2007), Akter (2008) and Akram and Olmstead (2011) for Pakistan, Islam, Kitawaki, and Rahman (1994), Chowdhury (1999), Ahmad, Goldar, Jakariya, and Misra (2002) for Bangladesh, Venkatachalam (2006) and Guha (2007) for India, Whittington, Pattanaak, Yan, and Kumar (2002) for Nepal, and Gunatilake, Yang, Pattanayak, & van den Berg, (2006) for Sri Lanka. Amongst the other CV studies in Asia, Calderon et.al (2006) assesses the WTP for improved watershed management in relation to water supply quality improvement in Manila, Wang, Xie and Li (2010) assesses WTP for water supply service in Chongqing, China and Lee, Yoo, and Kim (2013) estimate the WTP for water supply service in Korea.…”
mentioning
confidence: 99%